KEARIFAN LOKAL MASYARAKAT NELAYAN DI KAMPUNG TALISAYAN KECAMATAN TALISAYAN KABUPATEN BERAU - Puput Wahono; Gusti Haqiqiansyah; Erwiantono (2339-1324, 2021)
The purposes of this research are to study the characteristics of fishing communities, to learn the values of local wisdom contained in fishing communities. The sample method that used in this research is purposive sampling which was taken from 20 respondents. This research used the descriptive qualitative analysis method. In simply, the fishing communities in Talisayan village have slightly different characteristics, such as they put the male family members first before women in their meal time. All the tribe members do the tradition Buang Naas to throw away all dangers and bad luck. They have to keep their attitude, especially from speaking harsh words. They also cannot go to the sea on Friday or they believe they could get in danger. There are also some other rules and prohibitions that they follow such as prohibition to catch endangered species fish, littering the sea, cutting down mangrove trees, use bomb to catch the fish which can causing damage to the ecosystem underwater, etc. Techniques and technologies used by the fishing community in Talisayanare they use natural signs to predict the condition of the sea andthey still usethe traditional fishing gear. In terms of practices and traditions that are still being carried out is the management of local institutions in the form of fishermen's social gathering and for those fishermen who violates the rules by using bombs or explosivesto catch fish will be reported to police officers. Talisayan fishing areas are moved according to natural conditions.